Сакральна ритуальність у міфо-символічній образній системі прозової спадщини В. Барки - Вовк М. (Народна творчість та етнографія, 2005)
The article deals with principal aspects of Vasyl Barka’s outlooking model that is represented in the ritual and sacral sphere of his prose image system. The writer-mystic determines the functional ritual spectrum on the basis of folk religion moral as sacral act at the certain phases of human life (transfer rites), as psychotherapeutic phenomenon, and as necessary mechanism of explaining mystic link between the world of the alive and the dead. The strict observance of ritual acts, as Vasyl Barka states, is the sign of stability for collective and national memory mechanism.